Trophic Behavior of Specialist Predators from a Macroecological Approach: The Case of the Magellanic Woodpecker in South American Temperate Forests - Vergara-Egert, P; Fierro-Tapia, C; Moreira-Arce, D; Alaniz-Baeza, A; Carvajal-Leon, M (Elsevier B.V., 2020)
Theoretical and empirical studies have addressed predator-prey relationships, but the relevance of individual prey species, prey species richness and environment on the niche and the distribution of specialist predators have been scarcely tested with a macroecological approach. Here we aim to analyze the niche and spatial distribution of the Magellanic woodpecker (MWP; Campephilus magellanicus), a specialist predator, analyzing the relative importance of its individual prey species, prey species richness and environmental factors. We modeled the niches of the MWP and its five most important long-horned beetle prey species, quantifying their similarity in spatial distribution and niche. Then we evaluated the relative importance of single prey species and prey species richness on the potential distribution of the MWP, which showed a high degree of overlap with the niche and spatial distribution of three prey species. MWP models with each of these three prey species had a better fit than the model with prey species richness, and contributed more than environmental variables. These results suggest that MWP responds to particular prey items rather than prey species richness. These findings highlight the usefulness of ecological niche models to identify behavioral traits, being potentially replicable in other types of interactions such as competition, mutualism, parasitism, and pollination. © 2020 The Author(s)